TiNbCr multi-principal element alloy degradation behavior in harsh environments - Dainezi, Isabela (2024)
The new properties exhibited by multi-principal element (MPE) alloys demonstrate promising results that have relevance across various applications, particularly in strategic industries. A challenging aspect in the field of materials for harsh service environments involves designing alloys that are resistant to oxidation and sulfidation at high temperatures, especially those composed of refractory elements. While oxygen is abundant in the atmosphere, sulfur stands out as one of the most common corrosive contaminants in high-temperature industrial settings, including fuel and feedstocks. The primary objective of this study was to develop and characterize the microstructure, as well as investigate the oxidation and sulfidation behavior of the TiNbCr MPE alloy in both as-cast and hot-isostatically pressed (HIPed) conditions in air, oxygen, and a reducing H2S and H2 gas mixture at temperatures between 600 and 1100°C, with exposures up to 100 hours. The oxidation and sulfidation behavior of the TiNbCr MPE alloy was compared with that of the commercial Haynes 188. The results indicate that the MPE alloy exhibits significantly superior sulfidation resistance compared to the Haynes 188, exhibiting a parabolic behavior with slow kinetics attributed to the formation of a NbS2 inner layer facilitated by the addition of Cr. Notably, no formation of liquid products occurred, as observed in the case of Haynes 188. However, the oxidation behavior is linear, characterized by the formation of a non-protective scale, characterized as a stratified porous layer. Furthermore, in oxidation tests, it is observed a drop in the kinetics with an increasing at temperature-testing due to the formation of Cr2O3 layers.